2014
DOI: 10.1080/17470919.2014.925503
|View full text |Cite
|
Sign up to set email alerts
|

Preliminary investigation of the influence of dopamine regulating genes on social working memory

Abstract: Working memory (WM) refers to mental processes that enable temporary retention and manipulation of information, including information about other people (“social working memory”). Previous studies have demonstrated that nonsocial WM is supported by dopamine neurotransmission. Here, we investigated in 131 healthy adults whether dopamine is similarly involved in social WM by testing whether social and nonsocial WM are influenced by genetic variants in three genes coding for molecules regulating the availability … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
28
0
1

Year Published

2015
2015
2020
2020

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 14 publications
(31 citation statements)
references
References 68 publications
2
28
0
1
Order By: Relevance
“…In line with these findings, Val-homozygosity strongly modulated the pathway from ADHD to extreme antisocial behavior through the endophenotype of impaired social cognition in a large group of children aged around 7 years (N=4.365) and was associated with worse performance on social WM tasks compared to Methomozygotes (Langley et al, 2010;Dumontheil et al, 2014). In addition, Val-homozygotes performed worse on different aspects of social cognition such as openness to feelings and the ability to modulate feelings in oneself and others so as to promote personal understanding and growth (Lin et al, 2013).…”
Section: Val-homozygotes)mentioning
confidence: 55%
“…In line with these findings, Val-homozygosity strongly modulated the pathway from ADHD to extreme antisocial behavior through the endophenotype of impaired social cognition in a large group of children aged around 7 years (N=4.365) and was associated with worse performance on social WM tasks compared to Methomozygotes (Langley et al, 2010;Dumontheil et al, 2014). In addition, Val-homozygotes performed worse on different aspects of social cognition such as openness to feelings and the ability to modulate feelings in oneself and others so as to promote personal understanding and growth (Lin et al, 2013).…”
Section: Val-homozygotes)mentioning
confidence: 55%
“…There was a main effect of age group (Table ), with faster RTs in adults (1,840 ms ± 34) than adolescents (2,085 ms ± 31), and a significant interaction between age group and genotype (Table ). Similar to visuospatial WM, analysis of simple effects indicated that the effect of genotype was significant in adults ( F (1,302) = 7.12, p = .008, η p 2 = 0.023, see Dumontheil et al, ), with faster RTs in Met/Met individuals than Val carriers, but not in adolescents ( F (1,302) = 1.30, p = .255), where the pattern was in the opposite direction (Figure c). Simple effects analyses also indicated that the difference in social WM RT between Met/Met adults and Met/Met adolescents was greater ( F (1,302) = 22.10, p < .001, η p 2 = 0.068), than between adult and adolescent Val carriers ( F (1,302) = 6.60, p = .011, η p 2 = 0.021; Figure c), a pattern similar to that observed in the visuospatial WM task.…”
Section: Resultsmentioning
confidence: 82%
“…The predicted interaction between age group and genotype was significant (Table ). Simple effects analysis, indicated that the simple main effect of genotype was significant in adults ( F (1,324) = 8.95, p = .003, η p 2 = 0.027, see Dumontheil et al, ), with better performance in Met/Met individuals than Val carriers, but not in adolescents ( F (1,324) = 2.64, p = .106) where the direction of effects was in the opposite direction (Figure b). Analysis of the simple main effect of Age group indicated that Met/Met adults had higher visuospatial WM scores than Met/Met adolescents ( F (1,324) = 20.14, p < .001, η p 2 = 0.059), while Val carriers adults and Val carriers adolescents did not differ ( F (1,324) = 1.04, p = 0.308).…”
Section: Resultsmentioning
confidence: 89%
See 2 more Smart Citations